Sustaining Maternal and Neonatal Tetanus Elimination (MNTE) in countries that have been validated for elimination - progress and challenges - Nasir Yusuf; Robert Steinglass; Francois Gasse; Azhar Raza; Bilal Ahmed; Diana Chang Blanc; Ahmadu Yakubu; Christopher Gregory; Rania A. Tohme (BMC, 2022)
Abstract Background As of October 2021, 47 (80%) of the 59 countries, identified at highest risk for Maternal and Neonatal Tetanus (MNT), had been validated for elimination. We assessed sustainability of MNT elimination (MNTE) in 28 countries that were validated during 2011‒2020. Methods We assessed the attainment of the following MNTE sustainability indicators: 1) ≥ 90% coverage with three doses of Diphtheria-Tetanus-Pertussis vaccine (DTP3) among infants < 1 year, 2) ≥ 80% coverage with at least two doses of tetanus toxoid-containing vaccine (TTCV2 +) among pregnant women, 3) ≥ 80% protection at birth (PAB), 4) ≥ 70% skilled birth attendance (SBA), and 4) ≥ 80% first (ANC1) and fourth antenatal care (ANC4) visits. We assessed the introduction of TTCV booster doses. Data sources included the 2020 WHO /UNICEF Joint Reporting Forms, and the latest Demographic and Health Survey (DHS) or Multi-Indicator Cluster Surveys (MICS) for each country, if available. We reviewed literature and used DHS/MICS data to identify barriers to sustaining MNTE. Results Of 28 assessed countries, 7 (25%) reported ≥ 90% DTP3 coverage, 4 of 26 (16%) reported ≥ 80% TTCV2 + coverage, and 23 of 27 (85%) reported ≥ 80% PAB coverage. Based on DHS/MICS in 15 of the 28 countries, 10 (67%) achieved ≥ 70% SBA delivery, 13 (87%) achieved ≥ 80% ANC1 visit coverage, and 3 (20%) ≥ 80% ANC4 visit coverage. We observed sub-optimal coverage in many countries at the subnational level. The first, second and third booster doses of TTCV respectively have been introduced in 6 (21%), 5 (18%), and 1 (4%) of 28 countries. Only three countries conducted post-MNTE validation assessments. Barriers to MNTE sustainability included: competing program priorities, limited resources to introduce TTCV booster doses and implement corrective immunization in high-risk districts and socio-economic factors. Conclusions Despite good performance of MNTE indicators in several countries, MNTE sustainability appears threatened in some countries. Integration and coordination of MNTE activities with other immunization activities in the context of the Immunization Agenda 2030 lifecourse vaccination strategy such as providing tetanus booster doses in school-based vaccination platforms, during measles second dose and HPV vaccination, and integrating MNTE post-validation assessments with immunization program reviews will ensure MNTE is sustained.